Carbon footprint and embodied energy consumption assessment of building construction works in Western Australia - Biswas, Wahidul (Elsevier, 2014)
The Australian Green Infrastructure Council (AGIC) is currently leading a new approach to the delivering and operating of infrastructure through a more careful examination of the carbon footprint of construction activities. Using a life cycle assessment (LCA) methodology, this paper presents life cycle greenhouse gas (GHG) emissions and energy analysis of the Engineering Pavilion (hereinafter referred to as Building 216), at Curtin University Western Australia. The University utilises a Building Management System (BMS) to reduce its overall operational energy consumption.This LCA analysis employed a ‘mining to use’ approach, in other words, the analysis takes into account all of the stages up to the utilisation stage. The life cycle GHG emissions and embodied energy of Building 216 were calculated to be 14,229 tonne CO2-e and 172 TJ, respectively. This paper identified the ‘hotspots’, or the stages in production and operation of Building 216 that were the causeof the majority of the GHG emissions. From this, proposals for further improvements in environmental management may be made. The usage stage of the building produces 63% less GHG emissions than the University average, due to the implementation of the BMS. This system has played a significant role in reducing the total embodied energy consumption of the building (i.e., 20% less than the University average).